Defining the Corpus of Mapping Sciences Journals - Nedjeljko Frančula; Jadranka Stojanovski; Miljenko Lapaine (Kartografija i Geoinformacije, 2013)
The large number of journals and the constant changes which are happening in the world of scholarly publishing make it difficult to identify a group of journals relevant to a specific scientific field, particularly when dealing with a sub-field such as mapping sciences, which is inter-linked with many other disciplines. In this research, we form the corpus of active journals relevant to the mapping sciences and present their distribution by country, language of publication and level of accessibility. A systematic review of different subject-specific and multidisciplinary databases (GEOPHOKA, Bibliographia Cartographica, VINITI, GeoRef, Scopus and Web of Science), library catalogues, publishers’ web sites, professional associations’ web sites and other web resources was carried out. By applying set of criteria, a corpus of active journals in the field of mapping sciences was defined: it consists of 105 selected journals. The corpus of mapping sciences journals is described in detail, and the ISSN for each printed and online journal, the publisher, country, URL, language of publication and data on free accessibility are given. The largest numbers of mapping sciences journals are published in Germany, the United States of America and Poland. There are 53 journals in English language, while 44 are in open access. The limitations related to a lack of transparency of data on mapping sciences journals are discussed, as are questions of terminology.